Nanoimprinted 2D‐Chiral Perovskite Nanocrystal Metasurfaces for Circularly Polarized Photoluminescence. Issue 15 (4th March 2023) - Mendoza‐Carreño, Jose; Molet, Pau; Otero‐Martínez, Clara; Alonso, Maria Isabel; Polavarapu, Lakshminarayana; Mihi, Agustín
Abstract: The versatile hybrid perovskite nanocrystals (NCs) are one of the most promising materials for optoelectronics by virtue of their tunable bandgaps and high photoluminescence (PL) quantum yields. However, their inherent crystalline chemical structure limits the chiroptical properties achievable with the material. The production of chiral perovskites has become an active field of research for its promising applications in optics, chemistry, or biology. Typically, chiral halide perovskites are obtained by the incorporation of different chiral moieties in the material. Unfortunately, these chemically modified perovskites have demonstrated moderate values of chiral PL so far. Here, a general and scalable approach is introduced to produce chiral PL from arbitrary nanoemitters assembled into 2D‐chiral metasurfaces. The fabrication via nanoimprinting lithography employs elastomeric molds engraved with chiral motifs covering millimeter areas that are used to pattern two types of unmodified colloidal perovskite NC inks: green‐emissive CsPbBr3 and red‐emissive CsPbBr1 I2 . The perovskite 2D‐metasurfaces exhibit remarkable PL dissymmetry factors ( g lum ) of 0.16 that can be further improved up to g lum of 0.3 by adding a high‐refractive‐index coating on the metasurfaces. This scalable approach to produce chiral photoluminescent thin films paves the way for the seamless production of bright chiral light sources for upcoming optoelectronic applications. Abstract : Unmodified CsPbBr3 and CsPbBr1 I2 perovskite nanocrystals exhibit intense circularly polarized luminescence (CPL) reaching g lum values up to 0.15 and 0.3 (with a high index coating) when they are nanostructured into 2D chiral metasurfaces using soft nanoimprinting lithography. The approach is scalable and leads to large areas enabling CPL production from a variety of nanoemitters.